Platonin, a Cyanine Photosensitizing Dye, Inhibits Pyrogen Release and Results in Antipyresis - Jie-Jen Lee; Wu-Tein Huang; Dong-Zi Shao; Jyh-Fei Liao; Mao-Tsun Lin (Elsevier, 2003)
ABSTRACT: Intravenous injection of the supernatant fluids from human peripheral blood mononuclear cells (PBMC) incubated with lipopolysaccharide (LPS) caused fever in rabbits. The fever was in parallel with the levels of either interleukin-1β (IL-1β), IL-6, or tumor necrosis factor-α (TNF-α) in supernatant fluids. When incubating the platonin with the LPS-human PBMC, both the levels of IL-1β, IL-6, or TNF-α in supernatant fluids and the pyrogenicity of supernatant fluids were significantly suppressed. The febrile response to supernatant fluids from the LPS-stimulated PBMC was attenuated almost completely by adding anti-IL-1β, but not anti-IL-6 or anti-TNF-α, monoclonal antibody to supernatant fluids. In addition, both the fever and the increased levels of either IL-1β, IL-6, or TNF-α in rabbit serum following an intravenous administration of LPS were significantly attenuated by pretreatment with an intravenous dose of platonin. Furthermore, the fever induced by intravenous injection of IL-1β was reduced by pretreatment of rabbits with intravenous injection of platonin. The data indicate that platonin inhibits production of pyrogenic cytokines (in particular, IL-1β) from PBMC and results in antipyresis.